Antimicrobial Photodynamic Therapy (APDT) Action Based on Nanostructured Photosensitizers - Tedesco, Antonio C.; Primo, Fernando L. [UNESP]; de Jesus, Priscila da Costa Carvalho (Elsevier, 2017)
Important features are linked to the concept of antimicrobial photodynamic therapy (APDT). One approach is the need of effective strategies to overcome bacterial resistance to antibiotics. In this context, APDT has emerged as a valuable method, once cellular death is mediated by the production of reactive oxygen or nitrogen species (ROS or RNS), so it is very unlikely that resistant microorganisms may be selected. Another approach regards to photobiomodulation on wound healing for, simultaneously, antibacterial and remodeling tissue effects, as severe wounds are normally compromised by infection. APDT with appropriate photoactive nanodrugs specially designed for this purpose may contribute to both the wound regenerative process of the skin and at the same time protects and eradicates bacterial infections, accelerating the healing process with less or no side effects. Several issues are involved on APDT, among the design and choice of the nanostructured photosensitizer and how to certificate that it will penetrate the cellular cytoplasm or specific cellular organelles in the target tissue. For instance, Gram-positive bacteria are sensitive to APDT with a wide range of porphyrins and phthalocyanine compounds used as nanoencapsulated photosensitizers. On the other hand, Gram-negative have considerable resistance to the APDT process, as their external membrane may act as a barrier for permeability of the drug, besides being negatively charged. New efforts to overcome this barrier are under study with good results in the eradication of microorganisms, such as bacteria, fungi, viruses, and protozoa, by photoinactivation. Therefore, the selection of an ideal nanomaterial as drug delivery system is crucial to understand and develop more efficient APDT protocols based on the mechanisms of the antimicrobial inactivation.
Keywords: Antimicrobial photodynamic therapy; Laser inactivation; Nanobiotechnology; Photoprocesses; Photosensitizers; Phthalocyanine; Polymeric nanoparticles